Coupled Heat and Flow Analysis Inside a Diversion-Type Gas Heater With Vertical Guide Plate Structure - Guo, Yun; Zhang, Xuning; Zhou, Zhongwei (Frontiers in Energy Research, 2022)
In the natural gas heating process, the cylinder-type heater using water as an intermediate heating medium is the most extensively used. The heat exchange rate between the heating medium water and the fire and gas tubes in the great-capacity cylinder appears to be the most important element affecting a gas heater’s thermal efficiency. The water heat flow field within a new diversion-type gas heater with vertical guide plate design is described in this paper. In contrast to prior research that concentrated on natural convection heat transfer in medium water, the radiation impact is included. The discrete-ordinate model was utilized to build a 2-D combined natural convection and participating medium radiation heat transfer model, which was solved using the finite volume technique with unstructured body-fitted grids. First, experimental data were used to validate the numerical model. The coupled heat flow fields with vertical guide plates of various heights were then analyzed. The numerical findings reveal that utilizing a vertical guide plate structure, the proportion of radiation heat transfer in the total heat transfer rate reaches 25.1%, indicating that water radiation cannot be ignored. The vertical guide plate structure might help to create a well-organized flow pattern in the cylinder, which would improve natural convection heat transfer while having no influence on water radiation. Installing a vertical guide plate with a height of 550 mm and a thickness of 5 mm can lower the overall heat transfer rate in the convective tube bundle by 2.04%. In China, this technique has been given a patent.